An Inner Barrier to Career Development: Preconditions of the Impostor Phenomenon and Consequences for Career Development - Neureiter, Mirjam; Traut-Mattausch, Eva (Frontiers in Psychology, 2016)
The impostor phenomenon is increasingly recognized as an important psychological construct for career development, yet empirical research on how it functions in this domain is sparse. We investigated in what way impostor feelings are related to the fear of failure, fear of success, self-esteem, and the career-development aspects career planning, career striving, and the motivation to lead. We conducted two studies with independent samples of university students (N = 212) in a laboratory study and working professionals (N = 110) in an online study. In both samples, impostor feelings were fostered by fear of failure, fear of success, and self-esteem and they decreased career planning, career striving, and motivation to lead. A path analysis showed that impostor feelings had the most negative effects on career planning and career striving in students and on the motivation to lead in working professionals. The results suggest that the impostor phenomenon is relevant to career development in different ways at different career stages. Practical implications and interventions to reduce the negative effects of impostor feelings on career development are discussed.